The Influence of Clustering on MNE Location and Innovation in Great Britain - Gary Cook; Naresh Pandit; Hans Loof; Börje Johansson (European Regional Science Association (ERSA), 2010)
This paper addresses two questions: what, if anything, is the influence of geographic concentration of economic activity on patterns of foreign direct investment; what is the relationship, if any, between geographic concentration of economic activity, multinationality and innovation. The paper identifies the consensus view which is emerging in the literature, based on both theory and evidence, that strong clusters are likely to be attractive for inward direct investment and that they promote innovation. The paper tests whether this relationship is evident in Great Britain using data derived from the UKís Annual Foreign Direct Investment survey and the UKís Community Innovation Survey 2007. It addresses a surprising gap in the emerging literature by also examining the relationship between cluster strength and outward direct investment, thereby testing Porterís (1990) claim in The Competitive Advantage of Nations, that advantages gained in strong clusters would be the foundations of international competitiveness. The paper also distinguishes between two different types of agglomeration economy, localisation economies based on collocation of firms in related lines of activity, and urbanisation economies based on the overall concentration of economic activity in a particular region, a distinction most of the emerging literature in International Business has not made clear. The first set of models examine the propensity to engage in outward direct investment and the geographic pattern of foreign ownership of firms active in Great Britain and find that both are positively related to cluster strength, with localisation economies being more important than urbanisation economies. T wo models of innovation are estimated, the first examines what factors influence firms to be innovative and the second what influences innovation effort as measured by R&D intensity. In both cases there is evidence that regional agglomeration promotes innovation and that there are stronger effects flowing from own industry agglomeration than from broader regional scale.
Keywords: 330